Celebrating Adam Watkins First Birthday in Watkins' Backyard - Watkins, Howard::::::::: (1979)
Cindy the dog, Tom Shilton, Tony Correia, Dianne Shilton, Howard Watkins, Christine Watkins, Frances Kamp, Peggy Sanders, Laurie Leifer, ??? Guests seated under patio viewing televised video of Adam Watkins' birth